The multiculturalism practice in trend, factors and adaptation of employment of people with disabilities: a systematic review - Ab Karim, Noria; Hassan, Siti Aishah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
People with disabilities are acknowledged as part of multiculturalism in term of the diversity in their abilities. The aspect of acceptance, fairness, indiscrimination and freedom are counted in deciding whether the equality concept in multiculturalism being practiced or not. This article is a systematic review study which explores equality practice in employment of people with disabilities. Electronic database, ScienceDirect, is used to search relevant reading materials and 10 journals are found by considering the inclusion and exclusion criteria. The review is derived systematically from the trend of employment among people with disabilities, the factors that affect the chances of employment among disabilities and the adaptation of the people with disabilities in the world of work. Findings show that the main factor that is essential for employment opportunity is the type of disability. Implication for the workplace to accommodate includes modified working hours, modified duties and human support.